Phenomenology and lirical enunciation: Ortega, Ferraté, Gil de Biedma - Cabo Aseguinolaza, Fernando (Tropelías: Review of Literary Theory and Comparative Literature, 1995)
Taking into account the recognition of the influence of Phenomenology on Bispanic literary thought, this article draws attention to a particular part of this influence: The repercussions of the little known work by Ortega "Ensayo de estética a manera de prólogo" (1914) on Juan Ferraté’s theory of the lyric, towards the end of the nineteen fifties, which, consequentIy, left its mark on the work of Jaime Gil de Biedma. This aIlows us to take a closer look at the background to one of the theoretical approaches to the lyric which, even today, is of great interest in modern literary studies.